The Burden of Gastrointestinal Complaints in Kidney Transplant Recipients Using Tacrolimus With and Without Mycophenolate Mofetil: A Randomized Controlled Study - Fatly, Zainab Al; Betjes, Michiel GH; van Gestel, Judith; Verschragen, Marieken; de Weerd, Annelies E. (Frontiers in Nephrology, 2022)
Background Tacrolimus (TAC) combined with mycophenolate mofetil (MMF) is the immunosuppressive regimen in the majority of solid organ transplant recipients. Gastrointestinal complaints are frequent, which is considered predominantly a side effect of MMF. However, systematic research in this field is lacking. The aim of this study is to systematically investigate the burden of gastrointestinal complaints in TAC-treated kidney transplant recipients with and without MMF. Methods In a single-center, open-label, randomized controlled trial, low immunological risk recipients were randomized to either TAC and MMF or to TAC monotherapy from 6 months after kidney transplantation onwards [NTR4672],. They filled in the Gastrointestinal Symptom Rating Scale questionnaire, which covers five dimensions (abdominal pain, reflux, indigestion, constipation, and diarrhea), 6, 12, and 15 months after transplantation. Results Seventy-nine recipients were randomized and 72 completed all questionnaires (34 TACmono and 38 TAC/MMF). At baseline, the mean age was 59 years with 72% male, mean BMI 28 kg/m2, eGFR 55 ml/min/1.73m2, mean daily dose MMF 1200 mg and TAC 5.8 mg, with trough levels of 2.1 mg/L and 7.4 ug/L. Six months after transplantation, 75% of recipients reported troublesome symptoms (score ≥3). Diarrhea was the most troublesome (mean 3.3) and discontinuing MMF significantly reduced it (mean Δ score between month 6 and 15 TAC/MMF -0.9 vs. TACmono -1.8, p=0.03). In recipients with troublesome symptoms, abdominal pain (2.7 to 1.8, p=0.003), indigestion (2.8 to 2.3, p=0.012), and reflux (2.9 to 1.7, p=0.007) significantly decreased over time, independent of MMF use. Conclusion The majority of kidney transplant recipients with TAC and MMF experienced troublesome gastrointestinal symptoms 6 months after transplantation. While constipation remained troublesome, indigestion, abdominal pain, and reflux improved over time by month 15. Diarrhea only improved after discontinuing MMF.